2018
DOI: 10.1093/ije/dyy032
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of folic acid in pregnancy on offspring DNA methylation: follow-up of the Aberdeen Folic Acid Supplementation Trial (AFAST)

Abstract: BackgroundIt has been proposed that maternal folic-acid supplement use may alter the DNA-methylation patterns of the offspring during the in-utero period, which could influence development and later-life health outcomes. Evidence from human studies suggests a role for prenatal folate levels in influencing DNA methylation in early life, but this has not been extended to consider persistent effects into adulthood.MethodsTo better elucidate the long-term impact of maternal folic acid in pregnancy on DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 43 publications
3
60
0
3
Order By: Relevance
“…Our observation of inverse association in TT cases could be suggested as an outcome of impaired folate metabolism during development of TT embryos, eventually leading to altered DNA methylation at the lip prominences, and ultimately impairing their correct fusion. This observation of differential methylation at the lip prominences with functional variant in MTHFR gene is in line to previous supporting evidence linking folate metabolism and epigenetic modifications in the pathogenesis of nsCL/P (Richmond et al, ) and supports the hypothesis that both genetic and environmental factors can influence DNA methylation level in lip tissues (McKay et al, ; Sun, ).…”
Section: Discussionsupporting
confidence: 90%
“…Our observation of inverse association in TT cases could be suggested as an outcome of impaired folate metabolism during development of TT embryos, eventually leading to altered DNA methylation at the lip prominences, and ultimately impairing their correct fusion. This observation of differential methylation at the lip prominences with functional variant in MTHFR gene is in line to previous supporting evidence linking folate metabolism and epigenetic modifications in the pathogenesis of nsCL/P (Richmond et al, ) and supports the hypothesis that both genetic and environmental factors can influence DNA methylation level in lip tissues (McKay et al, ; Sun, ).…”
Section: Discussionsupporting
confidence: 90%
“…For example, Gonseth et al [29] observed an inverse correlation between periconceptional folate supplementation and methylation in newborns in that mostly hypomethylation events were observed with increasing maternal folate intake. This trend, though counterintuitive, is consistent with observations made on methylation sites in newborn DNA that associate with maternal plasma folate levels during pregnancy [30] and within offspring DMRs associated with lowand high-dose maternal folate supplementation [31].…”
Section: Discussionsupporting
confidence: 88%
“…36 This locus has also been described as a metastable epiallele as the imprinting of this region can be modulated by periconceptional environment and persist through adulthood. [37][38][39] Van Dijk et al have reported that hypomethylation in the VTRNA2-1 region in newborns was associated with a 2.1fold increased risk of childhood obesity compared with monoallelic methylation (95% CI 1.3-3.4, P = 0.002). 40 Some transgenerationally heritable DNA methylation marks have been associated with nearby genetic variation 14,41 but allele-specific methylation at VTRNA2-1 has not yet been linked to any underlying genetic variation.…”
Section: Resultsmentioning
confidence: 99%
“…Imprinted regions are often associated with tissue growth and a loss of imprinting (LOI) can be linked to tumorigenesis as shown for the H19/IGF2 region . This locus has also been described as a metastable epiallele as the imprinting of this region can be modulated by periconceptional environment and persist through adulthood . Van Dijk et al have reported that hypomethylation in the VTRNA2‐1 region in newborns was associated with a 2.1‐fold increased risk of childhood obesity compared with monoallelic methylation (95% CI 1.3‐3.4, P = 0.002) …”
Section: Discussionmentioning
confidence: 99%